2022
DOI: 10.1021/acsanm.2c04213
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Delivery of Exogenous Gene in Mature Plants Using Nuclear Location Signal and Cell-Penetrating Peptide Nanocomplex

Abstract: Delivery and expression of exogenous plasmid DNA (pDNA) into mature plants for plant genetic engineering mainly rely on Agrobacterium-mediated transformation and biolistic bombardment. Meanwhile, the process of pDNA entering the nucleus via traditional methods is random and there is no nuclear targeting effect. Here, we reported a dual-peptide-based gene delivery system to achieve nuclear delivery of exogenous pDNA in mature plants. This system is a combination of engineered peptides composed of nuclear locati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
(85 reference statements)
0
3
0
Order By: Relevance
“…Recent advancements in nanotechnology have revealed the potential of nanomaterials in facilitating the delivery of genetic materials, such as plasmid DNA 23−25 and siRNA, 26,27 as well as biomacromolecules like functional proteins, 28 active ingredients, 29,30 nutrients, 31 and therapeutics 32 in plants. Singlewalled carbon nanotubes (SWCNTs), 23,24,33 mesoporous silica nanoparticles (MSNs), 34,35 layered double hydroxide (LDH) clay nanosheets, 26 and functional peptide−DNA complexes 25,36 Several studies have demonstrated the possibility of carbon nanotube-mediated gene delivery in plant nucleus, 23,36 chloroplast, 24,33 and mitochondrial 25 genomes. However, there is a need to develop high aspect ratio nanomaterials for plant transformation that are degradable, biocompatible, and manufactured with controlled aspect ratios on a large scale.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Recent advancements in nanotechnology have revealed the potential of nanomaterials in facilitating the delivery of genetic materials, such as plasmid DNA 23−25 and siRNA, 26,27 as well as biomacromolecules like functional proteins, 28 active ingredients, 29,30 nutrients, 31 and therapeutics 32 in plants. Singlewalled carbon nanotubes (SWCNTs), 23,24,33 mesoporous silica nanoparticles (MSNs), 34,35 layered double hydroxide (LDH) clay nanosheets, 26 and functional peptide−DNA complexes 25,36 Several studies have demonstrated the possibility of carbon nanotube-mediated gene delivery in plant nucleus, 23,36 chloroplast, 24,33 and mitochondrial 25 genomes. However, there is a need to develop high aspect ratio nanomaterials for plant transformation that are degradable, biocompatible, and manufactured with controlled aspect ratios on a large scale.…”
mentioning
confidence: 99%
“…Recent advancements in nanotechnology have revealed the potential of nanomaterials in facilitating the delivery of genetic materials, such as plasmid DNA and siRNA, , as well as biomacromolecules like functional proteins, active ingredients, , nutrients, and therapeutics in plants. Single-walled carbon nanotubes (SWCNTs), ,, mesoporous silica nanoparticles (MSNs), , layered double hydroxide (LDH) clay nanosheets, and functional peptide–DNA complexes , have demonstrated delivery of functional DNA/RNA cargoes into plant cells without mechanical assistance. Several studies have demonstrated the possibility of carbon nanotube-mediated gene delivery in plant nucleus, , chloroplast, , and mitochondrial genomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation